THE APPLICATION OF THE NET PROMOTER SCORE (NPS) METHOD IN MEASURING CUSTOMER SATISFACTION IN THE RETAIL INDUSTRY IN MEDAN - Khairunnida; Renny Lubis; Rizaldy Khair (SEAN Institute, 2023)
The retail industry in Medan City is one of the most competitive industries. Tight business competition in the retail industry requires companies to constantly improve the quality of their products and services. Therefore, measuring customer satisfaction is very important for companies to find out the extent to which the quality of their products and services meets customer needs and expectations. Research Methods Net Promoter Score (NPS) is one of the popular methods used to measure customer satisfaction. This method allows companies to measure customer satisfaction using one simple question, namely